2019
DOI: 10.1186/s42444-019-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of diagnostic codes of major clinical outcomes in a National Health Insurance database

Abstract: Background and objectives: The Korean National Health Insurance Service (NHIS) database has been widely used for cardiovascular research. We validated the primary diagnostic codes of major clinical outcomes, including acute myocardial infarction (AMI), gastrointestinal bleeding (GIB), stroke, and intracranial hemorrhage (ICH) used for Korea NHIS claims. Subjects and methods: From 2016 to 2017, 800 patients with primary diagnostic codes of AMI, GIB, stroke, or ICH at discharge were randomly selected from a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 21 publications
(33 reference statements)
2
61
1
Order By: Relevance
“…Third, the data obtained from the claims data could not exclude the possibility of a diagnosis code inaccuracy and disease misclassi cation. Recent Korean studies that compared diagnosis from claim databases with medical records observed overall accuracy rates of 92.0% for MI, and 90.5% for ischemic stroke [28]. There was a possibility of non-differential misclassi cation which bias the risk ratio toward the null.…”
Section: Limitationsmentioning
confidence: 99%
“…Third, the data obtained from the claims data could not exclude the possibility of a diagnosis code inaccuracy and disease misclassi cation. Recent Korean studies that compared diagnosis from claim databases with medical records observed overall accuracy rates of 92.0% for MI, and 90.5% for ischemic stroke [28]. There was a possibility of non-differential misclassi cation which bias the risk ratio toward the null.…”
Section: Limitationsmentioning
confidence: 99%
“…Third, the data obtained from the claims data could not exclude the possibility of a diagnosis code inaccuracy and disease misclassification. Recent Korean studies that compared diagnosis from claim databases with medical records observed overall accuracy rates of 92.0% for MI, and 90.5% for ischemic stroke [ 28 ]. There was a possibility of non-differential misclassification which bias the risk ratio toward the null.…”
Section: Limitationsmentioning
confidence: 99%
“…MI was defined as a recording of ICD-10 codes I21 or I22 during hospitalization. Stroke was defined as a recording of ICD-10 codes I63 or I64 during hospitalization, along with claims for brain magnetic resonance imaging or brain computerized tomography [23]. We also performed analyses on composite endpoint including both MI and stroke.…”
Section: Clinical Outcomesmentioning
confidence: 99%